Hierarki Pengaruh Dalam Pemberitaan Gibran Sebagai Kandidat Walikota Surakarta Di Solopos.com - Pundra Rengga Andhita (Avant Garde, 2021)
This study aims to determine the hierarchy of influence in the reporting of Gibran Rakabuming Raka as a candidate for mayor of Surakarta on Solopos.com seen from the theory of the hierarchy of influence of the mass media. This study uses a qualitative descriptive method with an emphasis on collecting data through in-depth interviews, observation and literacy studies. The data analysis method used interactive analysis by Miles and Huberman through three stages, namely data reduction, data presentation and conclusion drawing. Data analysis in this study used triangulation. The results showed that the high frequency of reporting on Gibran's candidacy as a candidate for Mayor of Surakarta on Solopos.com did not indicate Solopos.com's dependence on Gibran. The publication of the news is influenced by various factors from each level of the hierarchy of influence. At the individual level, the professional value of journalists is more dominant than the personal political choice factor. At the level of routine media, it shows the opposite. There is an influence of media routines on Gibran's reporting, namely, the implementation of editorial meetings and gatekeeping, tiered supervision of news content. These two aspects play a role as quality control of news products produced by Solopos.com. At the organizational level, it shows that there are no internal (owners or media group networks) and external (advertisers or political forces) factors that influence Gibran's news coverage. Newsrooms are not intervened by media elites, owners or advertisers. At the extra media level, the emphasis is on the public's attention to Gibran, which is the main consideration for Solopos.com. Gibran is considered to have high news value. The ideological level places more emphasis on Solopos.com's efforts in building an ecosystem of media organizations that prioritize the quality of journalistic products that are actual, credible, informative, educative, solutive and varied.